2020
DOI: 10.1021/acs.energyfuels.0c01660
|View full text |Cite
|
Sign up to set email alerts
|

Demulsification of Water-Containing Crude Oil Driven by Environmentally Friendly SiO2@CS Composite Materials

Abstract: Relatively low cost, environmental friendly, and high-efficiency silicon dioxide/carbon sphere composite demulsifiers (SiO 2 @CS) were prepared via an in situ hydrothermal−calcination route. They were characterized by Fourier-transform infrared spectroscopy, field-emission scanning electron microscopy, energy-dispersive X-ray spectroscopy, and X-ray diffraction. The demulsifiers with different ratios of SiO 2 and CS were systematically investigated. The effect of the temperature, standing time, and dosage of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 35 publications
(60 reference statements)
1
13
0
Order By: Relevance
“…It is reported that the lower dynamic IFT was more beneficial to the DE improvement. 13,33 The result is consistent with DE of the polymers. It is concluded that the hyperbranched polymer molecules can effectively penetrate into the interface film to decrease the IFT and enhance the aggregation of water droplets.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…It is reported that the lower dynamic IFT was more beneficial to the DE improvement. 13,33 The result is consistent with DE of the polymers. It is concluded that the hyperbranched polymer molecules can effectively penetrate into the interface film to decrease the IFT and enhance the aggregation of water droplets.…”
Section: Resultssupporting
confidence: 86%
“…Therefore, it is extremely urgent to develop new efficient methods to separate the oil–water emulsion. Demulsification is a significant means to solve the separation problem of an oil–water emulsion in the petroleum and petrochemical industry. At present, the demulsification methods include mechanical demulsification, , electric demulsification, , chemical demulsification, and biological demulsification. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, demulsification and removal of water from crude oil are of great significance. At present, demulsification methods include centrifugation, microwave and heat treatment, membrane separation, flocculation, chemical demulsification, biological technology, and so on [8–14] . At present, chemical demulsification is the most commonly used demulsification method [15–17] .…”
Section: Introductionmentioning
confidence: 99%
“…At present, demulsification methods include centrifugation, microwave and heat treatment, membrane separation, flocculation, chemical demulsification, biological technology, and so on. [8][9][10][11][12][13][14] At present, chemical demulsification is the most commonly used demulsification method. [15][16][17] The chemical demulsifier is a kind of surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the recyclability test indicated that CNTs/ Fe 3 O 4 could be reused four times without significant reduction in light transmittance. Yuan et al [26] prepared an efficient SiO 2 @CS composite demulsifier by in situ hydrothermal calcination using glucose, tetraethyl protosilicate and water as raw materials. The demulsification experiment showed that when the dosage was 300 mg/L and the temperature was 70 °C, the demulsification efficiency of SiO 2 @CS-50 on the emulsion reached 89.52 % within 150 min.…”
Section: Introductionmentioning
confidence: 99%